Fractalkine is a “find-me” signal released by neurons undergoing ethanol-induced apoptosis - Sokolowski, Jennifer D.; Chabanon-Hicks, Chloe N.; Han, Claudia Z.; Heffron, Daniel S.; Mandell, James W. (Frontiers in Cellular Neuroscience, 2014)
Apoptotic neurons generated during normal brain development or secondary to pathologic insults are efficiently cleared from the central nervous system. Several soluble factors, including nucleotides, cytokines, and chemokines are released from injured neurons, signaling microglia to find and clear debris. One such chemokine that serves as a neuronal-microglial communication factor is fractalkine, with roles demonstrated in several models of adult neurological disorders. Lacking, however, are studies investigating roles for fractalkine in perinatal brain injury, an important clinical problem with no effective therapies. We used a well-characterized mouse model of ethanol-induced apoptosis to assess the role of fractalkine in neuronal-microglial signaling. Quantification of apoptotic debris in fractalkine-knockout and CX3CR1-knockout mice following ethanol treatment revealed increased apoptotic bodies compared to wild type mice. Ethanol-induced injury led to release of soluble, extracellular fractalkine. The extracellular media harvested from apoptotic brains induces microglial migration in a fractalkine-dependent manner that is prevented by neutralization of fractalkine with a blocking antibody or by deficiency in the receptor, CX3CR1. This suggests fractalkine acts as a ‘find-me’ signal, recruiting microglial processes toward apoptotic cells to promote their clearance. Next, we aimed to determine whether there are downstream alterations in cytokine gene expression due to fractalkine signaling. We examined mRNA expression in fractalkine-knockout and CX3CR1-knockout mice after alcohol-induced apoptosis and found differences in cytokine production in the brains of these knockouts by 6 hours after ethanol treatment. Collectively, this suggests that fractalkine acts as a ‘find me’ signal released by apoptotic neurons, and subsequently plays a critical role in modulating both phagocytic clearance and inflammatory cytokine gene expression after ethanol-induced apoptosis.